Changing new normal lifestyle in COVID-19 pandemic: Sabah, Malaysia - Mei,, Ching Lim; Syed Sharizman Bin Syed Abdul Rahim; Mohammad Saffree Jeffree; Nelbon Bin Giloi; Naing Oo Tha (Vol 5 | Issue 1 | Pages 146-151, 2021)
The COVID-19 pandemic threatens the world in the beginning of the 2020 [1,2]. The second wave of the Covid-19 infection in Malaysia during the 2nd week of March which was due to a mass religious gathering involving over 10,000 people from South East Asian countries in a confined area where a lot of close contacts took place, was the turning point for Malaysia when positive cases rocketed as a consequence of sporadic cases of transmission within local community all over Malaysia [3-5]. The need from that time was to break the chain of the virus and to further contain the spread of the virus especially among the vulnerable groups like the elderly people, individuals who have underlying chronic diseases, and also children population. On 10th April 2020, a further extension of the Movement Control Order (MCO) in the country was announced at that time. There were reminders from Ministry of Health endlessly to adapt to the new norms in the long run, for at least the coming 2 years in order to prevent the formation of new clusters.